Triple oxygen isotope signatures in evaporated water bodies from the Sistan Oasis, Iran. Issue 20 (29th October 2015) - Surma, J.; Assonov, S.; Bolourchi, M. J.; Staubwasser, M.
Abstract: Natural samples from water bodies in the arid and semiarid environment of the Sistan Oasis, Iran, demonstrate a systematic evolution of 17 O‐excess and δ 18 O as a result of nonequilibrium fractionation during extreme evaporation. Residual water samples exhibit a significant and systematic decrease of 17 O‐excess with progressive evaporation loss, reaching values of −160 per meg over a 35‰ range of δ 18 O. Waters from heavily evaporated volume‐limited natural bodies with limited or no recharge fall on the theoretically predicted isotopic evolution curve in agreement with ambient relative humidity of 30 to 35%. Recharged water bodies appear to follow a different trend. These new results demonstrate the potential of 17 O‐excess for the estimation of evaporation loss and ambient conditions in an arid environment. Key Points: Triple oxygen isotope evaporation trend demonstrated for the Sistan Oasis, Iran 17 O‐excess modeled from rH and δ 18 O of initial water and ambient vapor 17 O‐excess in naturally evaporated waters reflects mean rH and evaporation loss